Ordered Rape: A Principal–Agent Analysis of Wartime Sexual Violence in the DR Congo. (November 2015) - Schneider, Gerald; Banholzer, Lilli; Albarracin, Laura
Policy makers and academics often contend that organizational anarchy permits soldiers to perpetrate sexual violence. A recent United Nations report supports this thesis especially with regard to the massive sexual abuse in the Congolese civil war. We challenge the anarchy argument and maintain, based on a principal–agent framework, that opportunistic military commanders can order their soldiers to rape through the use of sanctions and rewards. Our qualitative and quantitative analysis of a survey of 96 Congolese ex-soldiers shows that ordered rape is more likely in organizations where soldiers fear punishment and in which commanders distribute drugs as stimulants.